The Making and Shaping of the Victorian Teacher - Larsen, M. author. aut Link
X, 232 p.
Keywords: Providing comparative and international contexts to understand the history of the making of the teacher in Victorian England, this is a compelling account of the development during this time of teacher training, inspections and certification - reforms which shaped the good teacher as a modern and moral individual.